Identification and characterization of roseltide, a knottin-type neutrophil elastase inhibitor derived from hibiscus sabdariffa - Nguyen, Giang Kien Truc (2018)
Plant knottins are of therapeutic interest due to their high metabolic stability and inhibitory activity against proteinases involved in human diseases. The only knottin-type proteinase inhibitor against porcine pancreatic elastase was first identified from the squash family in 1989. Here, we report the identification and characterization of a knottin-type human neutrophil elastase inhibitor from Hibiscus sabdariffa of the Malvaceae family. Combining proteomic and transcriptomic methods, we identified a panel of novel cysteine-rich peptides, roseltides (rT1-rT8), which range from 27 to 39 residues with six conserved cysteine residues. The 27-residue roseltide rT1 contains a cysteine spacing and amino acid sequence that is different from the squash knottin-type elastase inhibitor. NMR analysis demonstrated that roseltide rT1 adopts a cystine-knot fold. Transcriptome analyses suggested that roseltides are bioprocessed by asparagine endopeptidases from a three-domain precursor. The cystine-knot structure of roseltide rT1 confers its high resistance against degradation by endopeptidases, 0.2 N HCl, and human serum. Roseltide rT1 was shown to inhibit human neutrophil elastase using enzymatic and pull-down assays. Additionally, roseltide rT1 ameliorates neutrophil elastase-stimulated cAMP accumulation in vitro. Taken together, our findings demonstrate that roseltide rT1 is a novel knottin-type neutrophil elastase inhibitor with therapeutic potential for neutrophil elastase associated diseases.